Meningkatkan Budaya Kerja Positif Disiplin Kehadiran Guru di Sekolah Dengan Menggunakan Metode Reward And Punishment di SMP Negeri 1 Juwiring Kabupaten Klaten Tahun 2023 - Anik Indarti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
The reality shows that there are still teachers who do not have role models, especially in terms of pedagogy. Teachers often start lessons late for various reasons. This problem was discovered by researchers at SMP Negeri 1 Juwiring. After the questionnaire is distributed to respondents (students), the names of teachers who are often late will be collected. One way to overcome this problem is to provide training to increase teacher motivation to come to class on time. In this training, the Reward and Punishment method was applied with a positive work culture. When teachers (participants) have achieved the specified indicators, they will receive a reward, while teachers who have achieved the indicators will receive a punishment. The indicator of success in this research is that 100% of participants always arrive on time when starting lessons. This research uses the spiral method from Kemmis and Taggart. Kemmis and Mc model action research design. According to Taggart, there are four stages of action research, namely planning, action, observation and reflection. The data collection instruments were in the form of observation sheets for researchers and assessment sheets for participant attendance levels. The results of the research were that after carrying out positive culture training at SMP Negeri 1 Juwiring in cycle I, none of the participants had completed it. There is no participant who has succeeded 100% in not being late, but there is 1 participant whose accuracy level has reached 93%, this means that the participant has experienced improvement. Meanwhile, the accuracy rates for the other 4 participants ranged between 55%, 58%, 2% and 77%. After carrying out cycle II while continuing to use Reward and Punishment with a positive culture, 5 participants completed it.